The Responses of Muscle Damage Markers and Growth Mediator to Different Concurrent protocol of Endurance and Resistance Training - Khalid Mohamadzadeh salamat (Islamic Azad University, 2016)
Introduction: The aim of this study was to investigate the muscle damage markers and growth mediator responses to concurrent training with different endurance and resistance training order in healthy males. Methods: Thirty-nine healthy male were randomly assigned into three equal homogeneous groups; endurance-resistance training (ER), resistance- endurance concurrent training (RE) and control (C). The training group's subjects performed eight weeks 3sessions per week concurrent training sessions in the same intensity and duration but different by endurance and resistance exercise orders. Tow incremental exhaustive treadmill tests was performed before training and 72 h after the last training session. Blood samples for the measurement of creatine kinase (CK), lactate dehydrogenase (LDH), insulin-like growth factor (IGF)-1 and insulin-like growth factor binding protein (IGFBP)-3 were collected at baseline and immediately after the tow exhaustive treadmill tests. Results: The response of CK, LDH, IGF-1 and IGFBP-3 to the first and second incremental exhaustive treadmill test showed significant increases in both exercise orders when compared to baseline values (p<0.05). Also, comparison of pre and post-training responses showed a significant decrease in CK and LDH in both exercise order and a significant increase in IGFBP-3 and IGF-1 only in the RE exercise order (P<0.05). However, the present study results didn't show any significant difference between the ER and RE groups. Conclusion: According to the results, there were significant decreases in muscle damage markers after both types of concurrent training. However, higher growth mediator's responses were seen when resistance exercise precedes endurance exercise.